Temperature accuracy of an electric belt grill, a forced-air convection oven, and an electric broiler - Lawrence, T.E.; King, D.A.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated the temperature variation of an electric belt grill set at four temperatures, a forced-air convection oven set at three temperatures, and an electric broiler that has no temperature control. After finding that the actual temperatures of the electric belt grill and the forced-air convection oven were higher than the targeted temperature, we used regression techniques to correct for the temperature biases of both cooking methods. The forced-air convection oven was very precise when the doors were kept closed, as was the electric belt grill after adjustments were made. Temperature of the electric broiler was not consistent across surface positions or among replications. We suggest that when used for cooking experiments, each meat-cooking instrument be validated for temperature and corrected when necessary. This will improve cooking consistency and related results among various instruments and research institutions.
Keywords: Beef; Cooking; Temperature; Methods; Meat